(untitled) (Research, Society and Development, 2021)
The study aims to evaluate the difficulties faced by primiparous mothers in the breastfeeding process in Rooming-in at a Maternity Hospital in Porto Velho/RO. For the realization, it was opted for a field research with exploratory scope, descriptive with a qualitative approach. The research was conducted at the Mãe Esperança Municipal Maternity Hospital with 15 primiparous mothers, according to the inclusion and exclusion criteria, using the interview technique with a semi-structured script, considering the ethical and legal aspects of the research determined by Resolution 466/12 of the National Council of Health/Ministry of Health. The data were transcribed in full for analysis, respecting the confidentiality of the information. Through the statements, it was possible to identify that the mothers did not receive the necessary information about breastfeeding satisfactorily during the prenatal period, they had difficulties and were unable to clarify the benefits of this practice. It was highlighted that within the accommodation, the mothers received guidelines that were essential to continue the act of breastfeeding. It is concluded that it is necessary to promote this issue in order to increase discussions and encourage nurses to act in health education from prenatal care to the puerperal stage within the Accommodation, as the difficulty that puerperal women with regard to breastfeeding and its relevance.